Effect of Rectal Misoprostol to Blood Loss at High Risk Pregnancy - Daniel Liando, Daniel Liando; Manoe, IMS Murah; Moeljono, Eddy R (Indonesian Journal of Obstetrics and Gynecology, 2016)
Objective: To compare the effectiveness of rectal misoprostol administration to the amount of blood loss in 4th stage of labor at high risk pregnancy. Method: We recruited all pregnant women with high risk criteria including anemia, age  35 years old, or the number of pregnancies  4. Women would deliver appropriate to standard procedure of normal delivery. After that, we gave 400-mcg tablet of misoprostol rectally in treatment group. To count the amount of blood loss during 4th stage of labor, we put the underpad. Result: The amount of blood loss in 4th stage of labor in the treatment group was 201.1 (SD 80.3) ml less than the control group (285.9 (SD 93.2) ml). The result showed that the administration of 400-mcg misoprostol tablet rectally immediately after the birth of the placenta at high risk pregnancy impacted significantly to reduce the amount of blood loss in 4th stage of labor (p